Instructional Leadership and Academic Administration of School Administrators under the Pattani Primary Educational Service Area Office 2 - Saimuang, Amonrat (Al-HIKMAH Journal, 2022)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) เพื่อศึกษาภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 2) เพื่อศึกษาการบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 3) เพื่อเปรียบเทียบภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 จำแนกตามเพศ ตำแหน่ง ประสบการณ์ในการทำงานและขนาดสถานศึกษา 4) เพื่อเปรียบเทียบการบริหารงานวิชาการของผู้บริหารสถานศึกษาในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 จำแนกตามเพศ ตำแหน่ง ประสบการณ์ในการทำงานและขนาดสถานศึกษา 5) เพื่อศึกษาความสัมพันธ์ระหว่างภาวะผู้นำทางวิชาการกับการบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 6) เพื่อประมวลข้อเสนอแนะเกี่ยวกับความเป็นผู้นำทางวิชาการกับลการบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 กลุ่มตัวอย่าง ได้แก่ ผู้บริหารสถานศึกษา และครูผู้สอน จำนวน 295 คน ได้มาโดยวิธีการสุ่มตัวอย่างแบบง่าย เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม สถิติที่ใช้ ได้แก่ ค่าความถี่ ค่าร้อยละ ค่าเฉลี่ยเลขคณิต ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าที (t-test) การทดสอบค่าเอฟ (F-test) ทดสอบความแตกต่างรายคู่โดยใช้วิธีของบอนเฟอร์โรนี่ และค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน ผลการวิจัยพบว่า ภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 ภาพรวมอยู่ในระดับมาก การบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 ภาพรวมอยู่ในระดับมาก เปรียบเทียบภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 จำแนกตามเพศ ตำแหน่ง ประสบการณ์ในการทำงาน ภาพรวมแตกต่างอย่างไม่มีนัยสำคัญทางสถิติ เมื่อพิจารณาตัวแปรประสบการณ์ในการทำงาน พบว่า ด้านการจัดการด้านการเรียนการสอนแตกต่างอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 เมื่อพิจารณาจำแนกตามขนาดสถานศึกษาโดยภาพรวมและรายด้านแตกต่างอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 เปรียบเทียบการบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาจังหวัดปัตตานี เขต 2 จำแนกตามเพศ ตำแหน่ง ประสบการณ์ในการทำงานภาพรวมแตกต่างอย่างไม่มีนัยสำคัญทางสถิติ เมื่อพิจารณาตัวแปรประสบการณ์ในการทำงาน พบว่า ด้านการพัฒนาหลักสูตรสถานศึกษา ด้านการวัดผลประเมินผลและดำเนินการเทียบโอนผลการเรียนแตกต่างกันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 เมื่อพิจารณาจำแนกตามขนาดสถานศึกษาโดยภาพรวมและรายด้านแตกต่างอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 ความสัมพันธ์ระหว่างภาวะผู้นำทางวิชาการกับการบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 ภาพรวมมีความสัมพันธ์เชิงบวกอยู่ในระดับสูง (r=.940) อย่างมีนัยสำคัญทางสถิตที่ระดับ .01 เมื่อพิจารณาเป็นรายด้าน พบว่า ทุกด้านมีความสัมพันธ์เชิงบวกอยู่ในระดับสูง (r=.860 - .950) ยกเว้นด้านการวัดผลประเมินผลและดำเนินการเทียบโอนผลการเรียนมีความสัมพันธ์อยู่ในระดับปานกลาง (r=.535) ข้อเสนอแนะเกี่ยวกับภาวะผู้นำทางวิชาการกับการบริหารงานวิชาการของผู้บริหารสถานศึกษา ในสังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาปัตตานี เขต 2 ตามความคิดเห็นของผู้บริหารสถานศึกษาและครูผู้สอน ได้แก่ ผู้บริหารสถานศึกษาต้องกำหนดเป้าหมายและภารกิจของสถานศึกษาให้ชัดเจน จัดกระบวนการเรียนรู้โดยยึดนักเรียนเป็นสำคัญ จัดบรรยากาศที่เอื้อต่อการเรียนรู้ให้เหมาะสมกับวัยของนักเรียน ส่งเสริมให้ครูจัดทำแผนการจัดการเรียนรู้ทุกกลุ่มสาระการเรียนรู้ และใช้สื่อเทคโนโลยีทางการศึกษา เน้นการจัดทำวิจัยในชั้นเรียน มีการพัฒนาหลักสูตรสถานศึกษาอย่างต่อเนื่อง นิเทศการจัดกิจกรรมการเรียนการสอนแบบกัลยานมิตร ส่งเสริมให้ครูทุกคนเห็นความสำคัญของระบบประกันคุณภาพภายใน คำสำคัญ : ภาวะผู้นำ; ภาวะผู้นำทางวิชาการของผู้บริหารสถานศึกษา; การบริหารงานวิชาการ Abstract The objectives of this research were 1) to study the instructional leadership of school administrators under the Pattani Primary Educational Service Area Office 2, 2) To study the academic administration of school administrators under the Pattani Primary Educational Service Area Office 2, 3) To compare the instructional leadership of school administrators under the Pattani Primary Educational Service Area Office 2, 4) To compare the academic administration of school administrators under the Pattani Primary Educational Service Area Office 2, 5) To examine the relationship between the instructional leadership and the academic administration of school administrators under the Pattani Primary Educational Service Area Office 2, 6) To examine ways of developing the instructional leadership and academic administration of school administrators under the Pattani Primary Educational Service Area Office 2. The samples of the study are 295, comprising administrators and teachers under the supervision of Pattani Primary Educational Service Area Office 2, obtained by a simple sampling method. The research tool was a questionnaire. The statistics for analysis were frequency, percentage, average, standard deviation, t- test, F-test, Bonferroni test and Pearson Correlation. The findings were as follows. The instructional Leadership of school administrators under the Pattani Primary Educational Service Area Office 2, was at a high level in overall view. The academic administration of school administrators under the Pattani Primary Educational Service Area Office 2, was at a high level in overall view. The Comparison of instructional leadership of school administrators under the Pattani Primary Educational Service Area Office 2, classified by gender, position, work experience The overall picture was not statistically different. When considering the work experience variables, it was found that the teaching and learning management was significantly different at the .05 level. When considering classification by size of educational institutions as a whole and each aspect was significantly different at the .05 level. The comparison of academic administration of school administrators under the Pattani Primary Educational Service Area Office 2, classified by gender, position, and overall work experience, there was no statistically significant difference. When considering the variables of work experience, it was found that in terms of curriculum development, evaluation and measurement, and grade transferring were significantly different at the statistical level of .05. When considered classified by school size as a whole and each aspect was statistically different at the .05 level. The relationship between instructional leadership and academic administration of school administrators under the Pattani Primary Educational Service Area Office 2, overall, there was a high level of positive correlation (r=.940) with a statistical significance at the .01 level. When considering each aspect, it was found that all aspects had a high level of positive correlation (r=.860 - .950), except for the evaluation and measurement, and grade transferring were, there was a moderate correlation (r =.535) The ways of developing the academic leadership and academic administration of the school administrator under the supervision of Pattani Primary Educational Service Area Office 2 in the opinions of school administrators and teachers were school administrators have to clearly define the goals and missions of the educational institutions, focus on child center learning, environmental management contributed to learning of students, support and encourage teachers to design the lesson plan in all subjects and use educational technology, focus on classroom research, continually curriculum development, enhancement of amicable educational supervision and encourage all teachers understand the importance of the internal quality assurance system. Keywords: leadership; the instructional leadership; academic administration